The Effect of Financial Support on Academic Achievement and Retention of Female Engineering Students - Yang, Yang; Grauer, Bette (My University, 2016)
Engineering is one of the STEM (Science, Technology, Engineering, and Mathematics) fields in which women are severely underrepresented. Among those who do enter engineering, women are more likely to drop out of the major than men. Financial difficulty is among the top factors influencing retention of underrepresented students in engineering. Previous studies have examined the usefulness of different types of financial support for racial and gender minority students such as stipend, internship, and scholarship. This study focused on another type of financial support – a loan repayment award – and its influence on undergraduate women’s academic achievement and completion in College of Engineering at ____ University. Specifically, a private foundation ____ provided an incentive award to undergraduate women by offering to pay off subsidized student loans upon completion of an engineering degree. We examined whether this financial incentive upon graduation influenced achievement measured by GPA (grade point average) and graduation rates among female engineering students. This quantitative study used a pretest-posttest quantitative design. Forty sophomore women engineering students, matched by first generation status and ethnicity, were randomly placed into the experimental group (selected to receive repayment of their student loans on completion of an engineering degree) and the control group (not selected to receive loan repayment upon completion of an engineering degree). Students in the experimental group were told that their subsidized loans incurred during their time at _______ University would be paid off after graduation with an engineering degree. Students in the control group were not told about the program. The baseline grade point average (GPA), final GPA, graduation status, and demographic information were collected from all participants. Multiple statistical methods were used including independent t-test, analysis of covariance, and chi-square test. We found that (1) while the experimental group and the control group as a whole were very similar in terms of their average baseline GPAs, participants in the control group who successfully graduated with an Engineering degree had statistically significantly higher baseline GPAs than those who did not graduate; by contrast participants in the experimental group who graduated with an Engineering degree had very heterogeneous baseline GPAs. (2) The results from analysis of covariance showed that among those who graduated with an Engineering degree, the final GPAs between the experimental group and the control group were not statistically different after controlling for the baseline GPAs. (3) The experimental group completion rate was statistically significant higher than the control group. We concluded that the loan repayment award not only had a positive influence on completion rates, but also influenced completion by a greater variety of students in terms of GPA’s. Students in the experimental group had a wider range of GPA’s and lower mean GPA than the control group, suggesting that loan repayment may improve persistence for engineering students with lower GPA’s.
Citation: Yang, Y. L., & Grauer, B. (2016, June), The Effect of Financial Support on Academic Achievement and Retention of Female Engineering Students Paper presented at 2016 ASEE Annual Conference & Exposition, New Orleans, Louisiana. 10.18260/p.26136